let R be Ring; :: thesis: for I being Ideal of R
for a, b being Element of R
for x, y being Element of (R / I) st x = Class ((EqRel (R,I)),a) & y = Class ((EqRel (R,I)),b) holds
x * y = Class ((EqRel (R,I)),(a * b))

let I be Ideal of R; :: thesis: for a, b being Element of R
for x, y being Element of (R / I) st x = Class ((EqRel (R,I)),a) & y = Class ((EqRel (R,I)),b) holds
x * y = Class ((EqRel (R,I)),(a * b))

let a, b be Element of R; :: thesis: for x, y being Element of (R / I) st x = Class ((EqRel (R,I)),a) & y = Class ((EqRel (R,I)),b) holds
x * y = Class ((EqRel (R,I)),(a * b))

let x, y be Element of (R / I); :: thesis: ( x = Class ((EqRel (R,I)),a) & y = Class ((EqRel (R,I)),b) implies x * y = Class ((EqRel (R,I)),(a * b)) )
assume that
A1: x = Class ((EqRel (R,I)),a) and
A2: y = Class ((EqRel (R,I)),b) ; :: thesis: x * y = Class ((EqRel (R,I)),(a * b))
consider a1, b1 being Element of R such that
A3: x = Class ((EqRel (R,I)),a1) and
A4: y = Class ((EqRel (R,I)),b1) and
A5: the multF of (R / I) . (x,y) = Class ((EqRel (R,I)),(a1 * b1)) by Def6;
b1 - b in I by A2, A4, Th6;
then A6: a1 * (b1 - b) in I by IDEAL_1:def 2;
( (a1 - a) * b = (a1 * b) - (a * b) & a1 * (b1 - b) = (a1 * b1) - (a1 * b) ) by ;
then A7: (a1 * (b1 - b)) + ((a1 - a) * b) = (((a1 * b1) - (a1 * b)) + (a1 * b)) - (a * b) by RLVECT_1:28
.= (a1 * b1) - (a * b) by Th1 ;
a1 - a in I by A1, A3, Th6;
then (a1 - a) * b in I by IDEAL_1:def 3;
then ((a1 - a) * b) + (a1 * (b1 - b)) in I by ;
hence x * y = Class ((EqRel (R,I)),(a * b)) by A5, A7, Th6; :: thesis: verum